Host specific diversity in Lactobacillus johnsonii as evidenced by a major chromosomal inversion and phage resistance mechanisms. - Caitriona M Guinane (Public Library of Science (PLoS), 2011)
Genetic diversity and genomic rearrangements are a driving force in bacterial evolution and niche adaptation. We sequenced and annotated the genome of Lactobacillus johnsonii DPC6026, a strain isolated from the porcine intestinal tract. Although the genome of DPC6026 is similar in size (1.97 mbp) and GC content (34.8%) to the sequenced human isolate L. johnsonii NCC 533, a large symmetrical inversion of approximately 750 kb differentiated the two strains. Comparative analysis among 12 other strains of L. johnsonii including 8 porcine, 3 human and 1 poultry isolate indicated that the genome architecture found in DPC6026 is more common within the species than that of NCC 533. Furthermore a number of unique features were annotated in DPC6026, some of which are likely to have been acquired by horizontal gene transfer (HGT) and contribute to protection against phage infection. A putative type III restriction-modification system was identified, as were novel Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) elements. Interestingly, these particular elements are not widely distributed among L. johnsonii strains. Taken together these data suggest intra-species genomic rearrangements and significant genetic diversity within the L. johnsonii species and indicate towards a host-specific divergence of L. johnsonii strains with respect to genome inversion and phage exposure.